Curriculum Reform in the European Schools Towards a 21st Century Vision - Leaton Gray, Sandra (Springer International Publishing, 2018)
This open access book examines the modern role of the European School system within the European Union, at a time when the global economy demands a new vision for contemporary education. The European schools are currently in a state of crisis: their 60-year-old tradition of bilingual and multilingual education is being strained by rapid EU expansion and the removal of English speaking teachers as a result of Brexit. Their tried and tested model of mathematics and science education has rapidly been overtaken by new developments in pedagogy and assessment research, while recruitment and retention of students and teachers has become increasingly fraught as European member states review what they are, and what they are not, prepared to fund. The authors draw on original and empirical research to assess the European Schools' place in a new Europe where the entire post-war European Project is potentially at risk. This well-researched volume will be of interest to practitioners working in European schools as well as students and scholars of EU politics and international education.